Perlidungan Hukum Pekerja Alih Daya Untuk Mewujudkan Nilai Keadilan - Rohman, Abdul; I, Ismail; Setiawan, Puguh Aji Hari (Media Hukum Indonesia (MHI), 2025)
This study discusses the legal protection for outsourcing (outsourcing) workers in the perspective of social justice and employment law in Indonesia. The takeover phenomenon is widening with the enactment of the Job Creation Act which changed the previous regulatory structure, including the deletion of Articles 64 and 65 as well as the amendment of Article 66 in the Labor Code. These changes impact on the disappearance of transferable employment constraints, thus magnifying the potential for legal uncertainty and violations of workers’ normative rights. Through a normative juridical approach, this study analyzes the statutory provisions and the urgency of restricting the types of transferable work. It was stressed that legal protection should be preventive and repressive in order for workers to continue to receive justice, decent wages, as well as social security. The conclusion of the study recommends that the deleted articles be reinstated in order to guarantee equitable legal protection for turnover workers in accordance with Panchasila values and national employment objectives.